"The Notes Irom the Diary. Reminiscences" by M. Gorky - Kondiurina, E. (Literatūra, 1969)
The paper deals with the problem of defining the place which "The Nates from the Diary. Reminiscences" by M. Gorky occupies among the writer’s post-revolutionary writings. Entering into polemics with those who hold the view that in „The Nates" M. Gorky stepped back from the cardinal line of his creations, the author seeks to prove that in this book M. Gorky realizes the tendencies which were later fully expressed in „The Life of Klim Samgin".